Gadget Dan Generasi Z: Studi Kuantitatif Tentang Faktor-Faktor Penentu Keputusan Pembelian Di Marketplace Tokopedia - Iskandar, Muhammad Rivaldi; Stiadi, Muhamad; Kurniadi, Hanif (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of lifestyle, user convenience, and product variety on the purchasing decisions of gadgets and electronics on the Tokopedia marketplace by Generation Z in Kolaka Regency, both partially and simultaneously. This research uses a quantitative approach, with data collected through questionnaires distributed to 160 respondents who met the criteria. The results show that, partially, lifestyle does not have a significant effect on purchasing decisions, while user convenience and product variety do have a significant effect. Simultaneously, all three variables significantly influence purchasing decisions. These findings highlight the importance of system convenience and product diversity in driving the purchasing decisions of Generation Z, while also indicating that consumer lifestyle has not yet become a dominant determinant in purchasing behavior on the marketplace.